Dilated cardiomyopathy due to hypocalcaemia: a case report - Rupasinghe, Nilushka; Ranasinghe, Priyanga; Wanninayake, Leonard (Journal of medical case reports, 2024)
Background Hypocalcaemia is a rare, but reversible, cause of dilated cardiomyopathy causing heart failure. Several case reports have been reported on reversible cardiomyopathy secondary to hypocalcaemia. Case presentation We report a case of 54-year-old female Sri Lankan patient who presented with shortness of breath and was diagnosed with heart failure with reduced ejection fraction due to dilated cardiomyopathy. The etiology for dilated cardiomyopathy was identified as hypocalcemic cardiomyopathy, secondary to primary hypoparathyroidism, which was successfully treated with calcium and vitamin D replacement therapy. Conclusion This adds to literature of this rare cause of reversible cardiomyopathy secondary to hypocalcemia reported from the South Asian region of the world. This case highlights the impact of proper treatment improving the heart failure in patients with hypocalcemic cardiomyopathy.